The Successful Artificial Insemination with Frozen Semen from Different Genetic Qualities of Friesian Holstein Bull - Yekti, Aulia Puspita Anugra; Hasan, Ismail; Hermanto; Febrianto, Nanang; Isnaini, Nurul; Utami, Putri; Syah, Habib Asshidiq; Wahjuningsih , Sri; Susilawati, Trinil (Jurnal Ilmu-Ilmu Peternakan, 2024)
This study aimed to evaluate the success of artificial insemination (AI) using frozen semen with different genetic qualities of Friesian Holstein Bull. In this research, the bulls came from the artificial insemination center of Singosari, consisting of Friesian Holstein bulls with proven bull certificates and the pure breed from embryo transfer. The frozen semen was produced by standard semen processing in the artificial insemination center of Singosari. The inseminated female totals were 56 head of Friesian Holstein crossbred in Pujon district, Malang, Indonesia. The females were divided into two groups: 28 cows receiving insemination from frozen semen of proven bull (T1) and 28 from pure breed FH bull from embryo transfer (T2). The females were chosen with purposive sampling with the criteria, have a Body Condition Score (BCS) of at least 2.5 (scale 1–5), have normal reproductive organs, and exhibit the clear estrus sign. Artificial insemination was performed with a single dose at the eight hour after estrus. Semen deposition was at the corpus uteri, while the thawing process was performed at 22–23°C for 60 seconds. The result showed that the non-return rate 1 (NRR-1), non-return rate 2 (NRR-2), and conception rate (CR) values for AI using frozen semen from a proven bull were 96%, 75% and 43%, respectively. In contrast, the percentage of AI success using pure breed FH bull from embryo transfer was 93%, 86%, and 64%. In conclusion, AI success using pure breed FH bull from embryo transfer was better than proven bull frozen semen.